1992
DOI: 10.1177/019459989210600124
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Eosinophil in Head and Neck Cancer

Abstract: In a previous study, we found tumor-associated tissue eosinophilia (TATE) to be a favorable prognostic indicator for squamous cell carcinoma of the head and neck (p less than 0.05). The present expanded study was undertaken to confirm this finding. The pathology of 120 head and neck tumors was examined for histologic features suggestive of poor prognosis. Ten descriptive histopathologic variables, including two malignancy grading scales, were correlated with DNA flow cytometric data and clinical outcome. No co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1
9

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 26 publications
5
62
1
9
Order By: Relevance
“…4 In vitro, eosinophils can enhance the tumoricidal activity of macrophages 34 and in vivo, blood eosinophilia or eosinophil infiltration into some tumors is associated with improved prognosis. 3,7,8,35 Despite the overwhelming data showing that eosinophils are associated with numerous types of cancer, little is known about the molecular mechanisms required for localization of eosinophils to these sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In vitro, eosinophils can enhance the tumoricidal activity of macrophages 34 and in vivo, blood eosinophilia or eosinophil infiltration into some tumors is associated with improved prognosis. 3,7,8,35 Despite the overwhelming data showing that eosinophils are associated with numerous types of cancer, little is known about the molecular mechanisms required for localization of eosinophils to these sites.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that suggest that eosinophil tumor infiltration is associated with improved prognosis. 3,7,35 There are an equal number of studies showing either no role for eosinophils or an association with a poor prognosis. [42][43][44] Recently it has been suggested that eosinophils may not play a direct role in tumor cell clearance, but may instead participate in tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies have attempted to correlate TATE and cancer prognosis or to study the relationships between allergy-related disorders and cancer development (5,6). Even though the beneficial effect of TATE remains controversial, the presence of eosinophils appears as an indicator of good prognosis indicator in some cancers, such as head and neck cancers (7)(8)(9) and gastrointestinal cancers (10), particularly in colorectal cancers, in which high eosinophil counts were associated to increased 5-y survival (11). Clinical observations that eosinophil accumulation in intestinal tumors was associated to a better prognosis have been recently supported by experimental data in murine models (12)(13)(14).…”
mentioning
confidence: 99%
“…While IgG and IgM could induce antibody-dependent cellular cytotoxicity, opsonization for tumoricidal macrophages or complement-mediated lysis, there has been no data offered to support this. Eosinophilia has been observed in many human cancers 9,10 and as a positive prognostic indicator in some, [11][12][13][14][15][16] and rodent models show eosinophilic anti-tumor activity. 17 However, their role in the clinical tumor microenvironment is quite unclear.…”
Section: Sipuleucel-t (Provengementioning
confidence: 99%